MYUiTM: mobile app for efficient information sharing / Muhammad Norhafizie Mohd Isa and Siti Nuramalina Johari - Mohd Isa, Muhammad Norhafizie; Johari, Siti Nuramalina (College of Computing, Informatics, and Mathematics, 2024)
This study introduced the MyUiTM Mobile app as a groundbreaking solution tailored specifically for Universiti Teknologi MARA (UiTM) students, with the aim of revolutionizing information access and educational engagement. Developed using the Waterfall method, the app addressed the prevalent issue of fragmented information dissemination within the campus community. By providing a centralized platform, it facilitated seamless sharing of campus-related content, fostering a collaborative environment for knowledge exchange and resource discovery. Notably, its intuitive interface and integration with social media enhanced user experience. Recent testing had confirmed its high usability score of 75.5 on the System Usability Scale (SUS), highlighting its effectiveness in facilitating efficient information transmission. Ultimately, the MyUiTM Mobile app emerged as a pivotal tool in enhancing student learning, engagement, and information literacy at UiTM.